Política de expansão dos cursos superiores de tecnologia: nova face da educação profissional e tecnológica - Juliana Brito de Souza (2012)
This thesis sought to characterize the setting of the upper courses of technology within the process of democratization of access to higher education and, as well as analyzing whether the reasons listed in the legal documents for the choice of these courses are actually pointed by the students to join them. The exploratory research found that thepeculiarities of each institution, determined by several variables, be they human or materials are key elements for the understanding of a particular educational policy materializes in different ways. The proposal of the higher courses of technology cant be considered good or bad, a priori. The contribution of this thesis, though modest, is to clarify the new contradictions, tension, demands and contributions, showing features of one of the protagonists of the expansion of higher education in Brazil.From the literature review and of reports of graduates and students, the survey concluded that the higher courses of technology today little resemble the similar of decades of 1960 and 1970. Furthermore, by affording those who were excluded from the higher level of education, higher wages, greater employability and new perspectives of life, these courses can contribute to overcoming social, cultural and economic limitations. Regarding the profile of students, the thesis attests to thesymmetry between the profile listed in legal documents and the profile of dozens of students and technologists who contributed to this research to answer the questionnaires.